(untitled) (LACCEI, 2024)
This research aims to determine the effect of the application of Software Modellus in the learning of kinematics in students of Industrial Engineering of a Peruvian private university. Using a pre- and post-test experimental design, the Kinematics Graph Comprehension Test (TUG-K) was applied to 68 students during a training period and the level of learning achieved was determined using the Hake factor. The results were analyzed using the Shapiro-Wilk and Mann-Whitney U tests. The study showed that the application of Modellus significantly improves the learning of kinematics in the experimental group, obtaining a medium level for the Hake index (p ≤ 0.05), but regarding gender, better results were evidenced in the women of the experimental group (96%) than in the men. As for the results according to the "registration" variable, 95% of students who attend for the first time took advantage of the use of the software while second and third-enrollment students took advantage of it 100%. It is concluded that there is a significant increase in the average level in the learning of kinematics by applying the Modellus Software compared to traditional teaching with better results in female students and in first-enrollment students. It is recommended to implement the proposal in laboratory practices, form mixed groups and develop hybrid guides.